Effect of continuous theta burst stimulation on the glymphatic system, brain network and cognitive function in patients with cerebral small vessel disease - Dai, Pei; Yu, Hui-xian; Wang, Zhao-xia; Liu, Si-hao; Liu, Chang-bin; Xu, Guang-qing (Frontiers in Human Neuroscience, 2025)
ObjectiveWe aim to investigate the impact of continuous theta burst stimulation (cTBS) on glymphatic system (GS), brain network (BN) and cognition in cerebral small vessel disease (CSVD).MethodsThis exploratory study included a small cohort of 11 patients, divided into a cTBS group (6 patients) and a sham-cTBS group (5 patients). Over a period of 2 weeks, all participants underwent cTBS to the right dorsolateral prefrontal cortex (DLPFC). The efficiency of the GS was assessed by along the perivascular space (ALPS) index. BN was measured using global efficiency (GE), characteristic path length (CPL) and clustering coefficient (Cp). Cognition was evaluated by Montreal Cognitive Assessment (MoCA).ResultsIn the cTBS group, the ALPS index increased 4 out of 6 after treatment, compared to an increase in only 2 out of 5 in the control. Improvements in GE, CPL and Cp were observed in 4 out of 6 patients in the cTBS group, whereas no improvements were noted in the control group. The MoCA scores for all patients in the cTBS improved after treatment. Additionally, completion times of the Stroop color and word test C (Stroop C) were reduced for all individuals in the cTBS group, while the control saw an increase in one case. The Digital Span Test-backward (DST-backward) scores were significantly higher in the cTBS group than those in the control.ConclusionApplying cTBS to the DLPFC in CSVD may enhance the efficiency of brain glymphatic clearance, optimize network connectivity and improve cognitive function to a certain extent.